Staff Development Policy - Stout, Robert T. (Education Policy Analysis Archives, 1996)
It is argued here that staff development in the public elementary and secondary schools of the United States is misguided in both policy and practice. In its current form it represents an imperfect consumer market in which "proof of purchase" substitutes for investment in either school improvement or individual development. A policy model based on investment in school improvement is shown, in which different assumptions about how to improve schools are linked to different alternatives for the design and implementation of staff development. These are argued to be based on an investment rather than consumption model.